2019
DOI: 10.1002/jemt.23353
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of different irrigation protocols in removing tricalcium silicate‐based sealers from simulated root canal irregularities

Abstract: Objective The aim of this study was to evaluate the efficacy of different irrigation protocols in removing two tricalcium silicate‐based sealers from simulated root canal irregularities and root canal walls. Material and methods Root canals of 140 single‐rooted teeth were instrumented. In one‐half of each root, an apical groove was created. The samples were divided into two main groups (n = 70) based on the sealer used. In group 1, the grooves were filled with MTA Fillapex; in group 2, BioRoot RCS. The reassem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…These results also indicate that high-power sonic activation with EDDY of the novel DualRinse HEDP mixed with 3% NaOCl contributes to better canal wall cleaning at all root levels. This is in accordance with other studies using EDDY with other irrigants ( 1 , 20 , 21 ).…”
Section: Discussionsupporting
confidence: 93%
“…These results also indicate that high-power sonic activation with EDDY of the novel DualRinse HEDP mixed with 3% NaOCl contributes to better canal wall cleaning at all root levels. This is in accordance with other studies using EDDY with other irrigants ( 1 , 20 , 21 ).…”
Section: Discussionsupporting
confidence: 93%
“…The methodology of the present study is modelled on that of previous studies investigating the effect of irrigation techniques on the removal of root canal sealers [12,13,15]. In the current study, APJ sealer, a sealer which is widely used, and SSR sealer (CSBS) which has become popular in recent years due to its enhanced bonding ability, sealing ability and biocompatibility, were preferred.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown that irrigation agitation techniques remove more calcium hydroxide than CSI [22][23][24]. However, few studies have evaluated the removal of AH plus and CSBS from root canals by using irrigation agitation systems [12,13]. A study evaluated the effect of 4 different irrigation agitation systems in removing AH Plus sealer from root canals [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations